Causes and effects of domestic violence on survivors in Makusha suburb, Shurugwi - Chihoboya, Munyaradzi (Midlands State University, 2017)
The purpose of the study was to examine the causes and effects of domestic violence on the survivors in Makusha, Shurugwi. Both quantitative and qualitative methodologies were used in gathering the essential data related to this study. This included the use of questionnaires as well as in-depth interviews. The study was guided with Structuration and the Social learning theories as they help with relevant theoretical perspectives. The study’s findings confirmed that the major causes of domestic violence are primary social and economic and that most victims suffer most through emotional and physical consequences from the related abuse they are succumbed to. The study explored and established that survivors of domestic abuse rely largely on families and churches in dealing with domestic violence cases and hardly use the law because of various factors such as victims’ ignorance of the laws that protect them from abuse and societal attitudes towards the reporting cases of domestic violence as they it is viewed as a societal norm. Various recommendations were established and these include sensitization of traditional and religious leaders on Domestic violence and the various laws that protect victims and that stakeholders should conduct more workshops and awareness campaigns on domestic violence as well as on the Act itself